Deportation of non-citizen military veterans: A critical analysis of implications for the right to health. Issue 10 (3rd October 2018) - Horyniak, Danielle; Bojorquez, Ietza; Armenta, Richard F.; Davidson, Peter J.
ABSTRACT: Military personnel are commonly exposed to health-harming conditions during their service, resulting in higher rates of physical and mental health conditions compared with the general population. In an era of mass deportations, it is notable that non-citizen military veterans are not exempt from deportation. We utilised a human rights framework to conduct a critical analysis of potential health consequences of deportation for U.S. military veterans, identifying three ways in which veterans' rights to health may be constrained through deportation. First, honourably discharged deported veterans may be denied access to free or subsidised Veterans Affairs health services to which they would likely otherwise be entitled. Second, availability of and access to healthcare may be limited for reasons including barriers to enrolling in public insurance schemes, challenges navigating unfamiliar health systems and stigma and discrimination towards deported migrants. Finally, quality of available care may be sub-optimal due to limited expertise in service-related health issues and lack of evidence-based treatment for some health conditions (e.g. substance abuse/dependence). Binational multi-sectoral efforts are necessary to ensure that the rights to health of deported military veterans are adequately protected.